Digital Preservation Strategy For Research Data At The Center For International Forestry Research (CIFOR) With The Dataverse Repository - Rafa Aqilah; Nurmaya Prahatmaja; Kusnandar Kusnandar (IQRA`: Jurnal Perpustakaan dan Informasi, 2026)
_The forestry research data produced by the Center for International Forestry Research (CIFOR) consists of long-term observational data that is difficult to replicate. Therefore, if not managed with an appropriate digital preservation strategy, this data is at risk of being lost or becoming inaccessible. This study aims to examine the digital preservation strategy for research data through the Dataverse repository implemented by CIFOR. The research method used is a qualitative approach with a case study design. Data collection techniques include observation, interviews, documentation, and literature review. The results of this study indicate that CIFOR implements three of the six digital preservation strategies outlined by Deegan and Tanner (2006): software and hardware maintenance, refresh and backup, and migration. Technology maintenance is conducted selectively through evaluation prior to updating the Dataverse version. Refresh and backup activities enforce strict policies regarding preservation-friendly file formats, daily backups on the frontend server, and a disaster recovery strategy integrated with cloud servers and the headquarters in Nairobi. Meanwhile, migration is carried out from local (on-premise) servers to cloud-based services using containerization technology with Docker. As for the other three strategies emulation, digital archaeology, and conversion to analog formats, they were not implemented due to strict preventive policies in place from the very beginning of data deposit. The challenges faced by CIFOR include limited storage capacity due to the accumulation of log files, researchers’ perception that Dataverse procedures are too rigid, and limited human resources in the field of research data curation. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//